Relationship between Science Literacy and Disaster Preparedness: The Possible Role of Curriculum in Behavior Theories - Michael Cahapay; Rachel Patricia Ramirez (Asian Journal of Science Education, 2020)
While classical behavior theories assume that knowledge is linked to change in human behavior, there is a growing trend reporting the dissociation between these two constructs. This study aimed to determine the relationship between knowledge as measured by science literacy and behavior as represented by the disaster preparedness of the students.  It mainly employed a correlation research design involving 280 Grade VIII students in a public high school in the Philippines during the school year 2018-2019. The psychometric properties of the instruments used were established. The descriptive and inferential statistics provided the mean, percentage, standard deviation, and correlation coefficient for the variables under this research. Results showed that the students have a moderate level of science literacy and a low level of disaster preparedness. The results further revealed that there is a negative and weak relationship between the science literacy and disaster preparedness of the students. A broader explanatory context of this result is further discussed with the possible role of the curriculum. The conclusions and recommendations are offered in the paper.